THE BILINGUAL BRAIN AND THE SECOND LANGUAGE LEARNING - Aliva Rosdiana (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris)
The Bilingualism function in humans?? communication involves the brain work to produce languages. Bilingual people have their abilities to communicate into more than one language. There are two types of bilingualism, diglossia and code-mixing. Most of us consider bilingualism as something good, an advantage. For one thing, knowledge of another language enables people to communicate with members of other cultures in their own language. Forbidding the public use of a language and forbidding the formal teaching of a language is what governments can do in order to weaken the coherence of a cultural group so as to force integration. There are essentially two conditions according to which a person may become bilingual. Firstly, the two languages can be acquired sequentially. Secondly, the two languages can be acquired simultaneously. Points at stake related to language acquisition and learning, to mention some, are: where language is located in the brain and how it is encoded and decoded. Such demanding problems are among the interests of Neurolinguistics. Studies involving sophisticated brain imaging technologies called functional magnetic resonance imaging, fMRI, have revealed some intriguing patterns in the way brains process first and second languages. Studies and researches had better turn to neurological areas if they are ever to understand the nature of language acquisition and language processing. It is acknowledged that such issues can be useful not only to physicians and psychologists, but also to teachers in general. Keywords: Bilingualism, Brain, Neurolinguistics.